В – Z-переход в ДНК с нерегулярной последовательностью оснований - Миркин, С.С.; Лямичев, В.И.; Кумарев, В.П.; Кобзев, В.Ф.; Носиков, В.В.; Вологодский, А.В. (Биополимеры и клетка, 1987)
Рассматривается энергетика образования левоспиральной Z-формы в ДНК с произвольной последовательностью оснований. Кратко описана статистико-мехаинческая модель В – Z-перехода. Получены экспериментальные данные, позволившие определить все остававшиеся неизвестными параметры модели. Розглянуто енергетику утворення лівоспіральної Z-форми в ДНК з довільною послідовністю основ. Коротко описано статистико-механічну модель В–Z-переходу. Отримано експериментальні дані, що дозволяють визначати всі параметри моделі, які залишилися невідомими. The energetics of formation of the left-handed Z conformation in DNA with an arbitrary base-pair sequence is considered. A statistical-mechanical model of the B–Z transition includes three states for each base pair. The parameters of the model may be determined from comparison of the theory with experiment on the B–Z transition in synthetic inserts incorporated into supercoiled DNA. Four of six parameters of the model were determined before. To determine the rest two parameters a series of oligonucleotides has been synthesized and inserted into plasmid pUC19. The two-dimensional gel electrophoresis technique has been used to determine the superhelix density which induces the B–Z transition in the inserts. As a result a complete set of six energy parameters of the B–Z transition is known. The transition energy for a given base pair is shown to be independent of the neighbouring base pairs.